A Supermolecular Photosensitizer with Excellent Anticancer Performance in Photodynamic Therapy. (18th February 2014) - Liang, Ruizheng; Tian, Rui; Ma, Lina; Zhang, Lele; Hu, Yanli; Wang, Jian; Wei, Min; Yan, Dan; Evans, David G.; Duan, Xue
<x xml:space="preserve">Abstract</x> A supermolecular photosensitizer with excellent anticancer behavior when used for photodynamic therapy (PDT) is fabricated by the incorporation of zinc phthalocyanines (ZnPc) into the gallery of a layered double hydroxide (LDH). The composite material possesses uniform particle size (hydrodynamic diameter ∼120 nm), and the host–guest and guest–guest interactions result in a high dispersion of ZnPc in a monomeric state in the interlayer region of the LDH matrix, with high singlet oxygen production efficiency. In vitro tests performed with HepG2 cells reveal a satisfactory PDT effectiveness of the ZnPc(1.5%)/LDH composite photosensitizer: a cellular damage as high as 85.7% is achieved with a rather low dosage of ZnPc (10 μg/mL). An extraordinarily high specific efficacy is demonstrated (31.59 μg−1 (J/cm2)−1), which is over 185.5% enhancement compared with the previously reported photosensitizers under similar test conditions. Furthermore, an in vivo study of the ZnPc(1.5%)/LDH demonstrates excellent PDT performance with an ultra‐low dose (0.3 mg/kg) and a low optical fluence rate (54 J/cm2). In addition, the ZnPc/LDH photosensitizer displays high stability, good biocompatibility, and low cytotoxicity, which would guarantee its practical application. Therefore, this work provides a facile approach for design and fabrication of inorganic–organic supermolecular materials with greatly enhanced anticancer behavior.